2022
DOI: 10.1186/s13012-022-01231-6
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven approach to implementation mapping for the selection of implementation strategies: a case example for risk-aligned bladder cancer surveillance

Abstract: Background Implementation Mapping is an organized method to select implementation strategies. However, there are 73 Expert Recommendations for Implementing Change (ERIC) strategies. Thus, it is difficult for implementation scientists to map all potential strategies to the determinants of their chosen implementation science framework. Prior work using Implementation Mapping employed advisory panels to select implementation strategies. This article presents a data-driven approach to implementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Deciding which strategies to prioritize and which workgroups to work with is a critical next step. We plan to take a practical approach and focus on implementation strategies that are most endorsed by the study team and leadership [ 28 , 29 ]. Endorsement is currently completed informally through group discussion and consensus building, prioritizing implementation strategies that are both feasible and appropriate for the project.…”
Section: Discussionmentioning
confidence: 99%
“…Deciding which strategies to prioritize and which workgroups to work with is a critical next step. We plan to take a practical approach and focus on implementation strategies that are most endorsed by the study team and leadership [ 28 , 29 ]. Endorsement is currently completed informally through group discussion and consensus building, prioritizing implementation strategies that are both feasible and appropriate for the project.…”
Section: Discussionmentioning
confidence: 99%
“…A complexity-informed approach identified that user and persona testing (strategy 4.1) may be the single most impactful leverage point to support digital health implementation for people with ABI, reflecting findings from a recent systematic review highlighting the potential to address the complexities for “adopters” [ 41 ]. The fruitful use of VNA in this study directly addresses an identified need in implementation science for data-driven methods to prioritize and select implementation strategies from long lists of possibilities [ 82 ], especially given potential time and resource constraints. In addition, a focus on strategy 4.1 to target diverse considerations in the “condition” domain offers specific guidance on how to address a previously identified gap in implementation knowledge for people with ABI who have comorbidities and additional challenges [ 41 ], specifically, how to practically address the complexity of ABI, rather than reduce it through participant exclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…As bladder cancer recurrence is a significant concern for patients and healthcare providers, various methods have been developed to predict and monitor the likelihood of recurrence. While computer-aided assessment of the primary tumor has been shown to be predictive of likelihood for recurrence 41,42 , this examination presents only a snapshot in time, which could be augmented by repeated urine cytology exams [43][44][45] . However, there is currently little to no research on how repeat urine cytology exams can be leveraged to derive longitudinal markers of recurrence [46][47][48][49] .…”
Section: Introductionmentioning
confidence: 99%